Annealing‐promoted unidirectional migration of organic‐modified nanoparticles embedded two‐dimensionally in polymer thin films. Issue 45 (7th August 2015) - Liu, Yang; Kato, Takumi; Kubo, Masaki; Sugioka, Ken‐Ichi; Tsukada, Takao; Takami, Seiichi; Adschiri, Tadafumi
ABSTRACT The spatial structures of oleic acid‐modified CeO2 nanoparticles in polystyrene (PS) thin films spin‐coated on silicon substrates were observed by transmission electron microscopy, when the films underwent thermal annealing above the glass‐transition temperature of PS. Before annealing, the nanoparticles have segregated to the surface of the films, and formed two‐dimensional spatial structures in the PS films. Then, the nanoparticles migrated away from the film surface to the substrate/film interface during thermal annealing, maintaining the two‐dimensional spatial structures. In addition, we demonstrated that such unidirectional migration of nanoparticles across the PS film occurs regardless of the characteristics of the substrate surface, the concentration of nanoparticles, and the thickness of the films. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42760.